Pengaruh Pemberian Reward Dan Punishment Terhadap Hasil Belajar Materi Ipas Kelas V - Monica, Cindy; Parluhutan Tambunan, Husna; Siregar, Arifin; Tamba, Robenhart; Usman, Khairul (PGSD FKIP UPR, 2025)
This research aims to determine the effect of providing rewards and punishment on the learning outcomes of class V students at SD Negeri 023972, Binjai City District, FY 2023/2024. The population of this study was all 40 class V students. The sample used in this research is saturated sampling, in this case the researcher takes all members of the population to be used as samples. In this research, researchers used experimental research using the Quasi Experimental Design method, where the research cannot provide full control, using a Nonequivalent Control Group Design. The results of this research show that There is an influence of giving rewards and punishments on student learning outcomes in science and science subjects for class V students at SDN 023972 Binjai City Region FY 2023/2024.